Extracting Clinically Relevant Data from Biomechanical Modeling of Surgical Treatment Options for Spinal Injury in Damaged Vertebrae Th10, Th11 - Donnik, Anna M.; Ivanov, Dmitriy V.; Kireev, Sergey I.; Kossovich, Leonid Yurevich; Ostrovsky, Nikolay V.; Norkin, Igor A.; Levchenko, Kristina K.; Likhachev, Sergey V. (Известия Саратовского университета. Новая серия. Серия Математика. Механика. Информатика, 2019)
Two three-dimensional geometric solid-state models of the Th7-L1 spinal segment (Model 1, Model 2) with metal construction were built. Models include the vertebrae Th7, Th8, Th9, Th10, Th11, Th12, L1, intervertebral discs, facet joints and ligaments, and metal construction elements. In Model 1, the cortical and spongy layers are constructed by three-dimensional solids, facet joints and intervertebral discs by three-dimensional bodies, ligaments by one-dimensional objects. In Model 2, the spongy layer of bone tissue is built with a three-dimensional solid body, the cortical layer with a shell 1 mm thick, the facet joints and intervertebral discs with three-dimensional bodies, and the ligaments with one-dimensional ones. Bodies are accepted linear, isotropic, homogeneous. The mechanical properties of all biological tissues and metal are set on the basis of published data. The problem of the statics of an elastic body is solved. The fields of complete displacements and Mises equivalent stresses are obtained for each point of the constructed models under characteristic loads. The analysis of the field of equivalent stresses makes it possible to identify areas of the spine that are most susceptible to destruction. The analysis of the field of full displacements makes it possible to evaluate the stability and reliability of fixation under standard physiological loads.